THE PRACTICE OF UDDER ENGINEERING IN LIVESTOCK TRADE WITHIN URBAN MEDAN COMMUNITIES: PERSPECTIVE OF SHARIA ECONOMIC LAW - Ulum Harahap, Haddad (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2024)
Animal trafficking in Medan City often involves illegal practices, including udder engineering. This research aims to analyze this practice within the framework of Sharia economic law, particularly through the lens of relevant Hadiths, and to provide actionable recommendations based on the findings. A qualitative approach, utilizing literature analysis, was employed to gather data from Hadiths, fatwas of Islamic scholars, and related Sharia economic law literature. The analysis was conducted both descriptively and analytically to explore the Sharia implications of udder engineering. The results indicate that udder engineering is a form of fraud explicitly prohibited in Islam. A Hadith narrated by Abu Hurairah forbids the mixing of milk from camels or goats to deceive buyers, allowing them to return the animal within three days if deceived and receive compensation. Sharia economic law emphasizes honesty, fairness, and transparency in trade. Udder engineering violates these principles by deceiving buyers, constituting a form of tadlis (fraud) that is prohibited in Islamic law. The study concludes that udder engineering not only undermines market trust and integrity but also directly contravenes key principles of Sharia economic law, particularly those related to honesty and fairness in transactions.